` MODELING ABOVEGROUND BIOMASS ACCUMULATION OF COTTON - B. Jia; H. B. He; F. Y. Ma; M. Diao; G. Y. Jiang; Z. Zheng; J. Cui; H. Fan (Journal of Animal and Plant Sciences, 2014)
The objective of this study was to develop an improved model for describing the accumulation of aboveground cotton biomass. The model input was RTEP, which was the normalized product of thermal effectiveness and photosynthetically active radiation. The model was calibrated using data from field plots with five N rates and two cotton cultivars. Model validation was conducted using data from three independent cotton fields. Eight nonlinear functions described cotton growth well (R>0.0.894, SD<0.05). The parameters of the functions were then compared and the results indicated that the Richards function best fit the nonlinear relationships in a biologically meaningful way. The equation was as follows: relative aboveground biomass accumulation (RAGBA) = 1.024/(1+e6.646-10.115RTEP)1/1.417 (r = 0.981, s = 0.043). Validation results indicated that the root mean square error was 0.659 t hm-2, the relative error was 5.337%, the coefficient of concordance was 0.988, and the coefficient of determination was 0.961. The second derivative of the optimized model showed that in cotton, the process of aboveground biomass accumulation could be divided into three phrases using two inflection points. When the accumulation rate of the aboveground biomass of cotton was at its maximum, the relative product of thermal effectiveness and PAR was 0.622, the maximum rate of the aboveground biomass accumulation was 2.299, and the aboveground biomass accumulation was 0.549. In conclusion, our study indicates that the product of thermal effectiveness and PAR is a valuable parameter for estimating aboveground biomass accumulation in cotton.
Keywords: Cotton; Aboveground biomass accumulation; Product of thermal effectiveness and PAR (TEP); Normalization; Richards Model